Improve Reading Skills through the Medium of Clever Box on the Age 4-5 Years in Kindergarten: Meningkatan Kemampuan Membaca Melalui Media Clever Box Pada Usia 4-5 Tahun di KB-TK - Umi Nur Sholikah; Choirun Nisak Aulina (Academia Open, 2022)
Ability to read has a role which is important for a child's life early because introduce letters to children is the initial step son is able to read and to make a word. This research aims to know the application and the results of the media “Clever Box” against the enhancement of reading in a child group A. This research uses the Research Action Class as one approach to improve the ability to read the child. Implemented in a 2-cycle is divided into three levels namely prasiklus, cycle I and cycle II to get the result with the expected. In the pre cycle yields the value of the prosentase range of actions is as big as 39,66% whereas in cycle I prosentase increased by 61,15% until acquired prosentase value to be 60,34 which means no avail. Then research further by giving the action in cycle II, after having done research on the cycle II of this value prosentase kecapain action be 84,49%, up from the procurement value prosentase in cycle I and cycle II experienced an increase as large as 23,34%. With this can be seen from the comparison between cycle I and II for the research progresses. From the results obtained there is an increase that proves that with the use of the media “Clever Box” can improve the ability of the child's reading.